Restoration of Radiological Parameters with Fragment Specific Fixation for Distal Radius Fractures: A Case Series (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To assess the radiological outcomes of fragment-specific fixation for complex distal radius fractures.Methods: We conducted a retrospective case series of patients presenting with complex distal radius fractures and undergoing fragment-specific fixation between 1st January 2018 and 31st December 2019. Demographic information and mechanism of injury were recorded. Pre- and post-operative radiographs were analysed for fracture type, radial height, radial inclination, and palmar tilt.Results: A total of 15 patients were included in the study with a mean age of 40 ± 10 years. Most common mechanism of injury was RTA (67%) followed by fall. The most common fracture was noted to be AO type C3.1t (33%). A significant improvement in radial height and radial inclination was noted post-operatively (P-values = 0.014 and 0.038 respectively). Mean palmar tilt improved from 0.44° ± 17.5° preoperatively to 7.11° ± 6.64° post-operatively.Conclusion: Fragment-specific fixation is an effective treatment option for complex distal radius fractures with the ability to restore normal radiological parameters after surgery.